The Role of Internet Access for Business Owners in Accessing Kredit Usaha Rakyat (KUR) in Semarang City - Aqiel Farhan Hafizh Wahid; Ariska Nurfajar Rini (Universitas Diponegoro, 2024)
This research aims to analyze how internet access affects business owners' decisions to access KUR in Semarang City. The methodology used in this study is quantitative, employing logistic regression analysis with marginal effects, utilizing secondary data from the National Economic and Social Survey (SUSENAS) of Semarang City conducted in 2021. The results reveal a robust positive and statistically significant relationship between internet access and business owners' decisions to access KUR. The availability of the internet equips individuals with valuable resources, information, and a seamless application process, all of which contribute to a heightened inclination towards KUR utilization. Additionally, other variables that demonstrate significant influence include gender, household size, and homeownership status.